2015
DOI: 10.3997/2214-4609.201412455
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sensor Towed Streamer: From Concept to Fleet-Wide Technology Platform

Abstract: discuss the lessons learnt from the roll out of dual-sensor technology in PGS' fleet.T he launch of the dual-sensor towed streamer technology in 2007 is seen by many in the industry as the most important milestone in marine seismic technology in the last decade. The introduction of the technology triggered a significant interest and demand for broader bandwidth seismic data and increased the industry-wide awareness of the geophysical benefits of such broadband data for both frontier exploration and production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In recent years, VS have also been used on towed streamers for the elimination of surface reflections (ghosts); however, details of these developments have limited publicity as they contain commercially sensitive information. It was also concluded that VS allowed us to operate surveys closer to the bottom, increasing the signal-to-noise ratio (SNR), hence enhancing the system seismic imaging performance [23], [24]. Recently, the usage of mobile platforms for seismic geophysical surveying, mainly those where the streamers are installed in AUVs, is subject of attention, in particular in the European project WiMUST [25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, VS have also been used on towed streamers for the elimination of surface reflections (ghosts); however, details of these developments have limited publicity as they contain commercially sensitive information. It was also concluded that VS allowed us to operate surveys closer to the bottom, increasing the signal-to-noise ratio (SNR), hence enhancing the system seismic imaging performance [23], [24]. Recently, the usage of mobile platforms for seismic geophysical surveying, mainly those where the streamers are installed in AUVs, is subject of attention, in particular in the European project WiMUST [25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, a new version was introduced that is also able to pass three-wing birds. SCUs were initially used only during line changes and no data recording, but the introduction of a noise removal algorithm has enabled online operation which has now become standard (Widmaier et al, 2015). Although this device has served us well, its usage depends on allowable workboat weather.…”
Section: Introductionmentioning
confidence: 99%
“…In sea surveys in particular, water-bottom cables with such sensors have been used for the attenuation of water-column reverberations [ 11 ]. In recent years, vector sensors have been used on towed streamers for the elimination of surface reflections (ghosts) [ 12 ], however details of these developments have limited publicity as they contain commercially sensitive information. A further advancement in marine geo-acoustic surveys is the replacement of the ship-towed streamers with sensors either towed or carried by Autonomous Underwater Vehicles (AUV).…”
Section: Introductionmentioning
confidence: 99%